The Impact of Fulvic Acid on the Growth Physiology, Yield, and Quality of Tomatoes Under Drought Conditions - Hongxia Song; Weilong Zhu; Ziqing Guo; Tianyue Song; Jiayu Wang; Chongzhen Gao; Hongtao Zhang; Ruixue Shen (Agronomy)
Increased global drought severity threatens crop yield and quality. Fulvic acid (FA), a humic acid compound, enhances crop stress tolerance. This study investigated FA application on drought-stressed tomato ‘Provence’ during the seedling and fruiting stages. Seedling-stage drought severely inhibited growth, physiology, biochemistry, and photosynthesis, reducing seedling quality. Subsequent fruiting-stage drought further significantly decreased photosynthetic efficiency and assimilate synthesis, drastically lowering fruit yield and quality. FA application mitigated drought damage, with 400 mg·L−1 being optimal. At this concentration, under seedling drought, Seedling strength index (Si), Photosynthetic efficiency (Pn), and Instantaneous water use efficiency (IWUE) increased significantly by 76.54%, 67.46%, and 36.97%, respectively, with no adverse morphological effects by flowering. Post-drought FA spraying later significantly enhanced leaf photosynthetic enzyme activity and WUE (by 89.16%, 98.48%, 42.20%, and 40%), boosting Pn, promoting assimilate accumulation and transport to fruits. This resulted in significantly improved fruit yield and comprehensive quality. In conclusion, spraying 400 mg·L−1 FA significantly enhances tomato drought tolerance and water use efficiency in arid/semi-arid regions, offering an effective strategy for saving irrigation water and improving crop productivity in water-scarce areas.